Temporary Gasserian ganglion stimulation utilizing SNM electrode in subacute herpetic trigeminal neuralgia - Niu, Jiejie; Wang, Chenhui; Wang, Xing; Lu, Guijun (Frontiers in Neurology, 2024)
Objective: Gasserian ganglion stimulation (GGS) is a neuromodulation technique in treating postherpetic trigeminal neuralgia. Few research investigated temporary GGS for the treatment of acute/subacute herpetic trigeminal neuralgia. Besides, previous studies reported lead dislocation when utilizing traditional electrodes, which was associated with poor pain relief.dislocation. Preventing the accidental displacement of the lead following implantation has consistently been a primary objective in GGS research. Methods: We reported a 70-year-old female patient with subacute herpetic trigeminal neuralgia, who underwent temporary GGS for 14 days utilizing a quadripolar tined SNM lead. Computed tomography guided percutaneous foramen ovale puncture and temporary SNM electrode implantation were performed during the surgery. 12-month follow-up was recorded through telephone interview. Results: Zoster-related trigeminal pain was assessed as 9/10 on the visual analog scale (VAS) upon admission. After a 14-day GGS treatment, the VAS score was reduced to 1/10 at discharge but increased to 4/10 at the 12-month follow-up after surgery. Additionally, the anxiety level improved from 58 points to 35 points on the Self-Rating Anxiety Scale (SAS), and the depression level improved from 62 points to 40 points on the Self-Rating Depression Scale (SDS). The Physical Component Summary (PCS) score of the SF-12 increased from 33.9 to 47.0, while the Mental Component Summary (MCS) score of the SF-12 improved from 27.4 to 41.9. Conclusion: Temporary GGS might be a potentially effective treatment for subacute herpetic trigeminal neuralgia and SNM electrode might be a good choice for reducing the risk of dislocation.